STYLISTIC ORGANIZATION OF THE LEXICAL AND SYNTACTIC SPACE OF THE POETIC WORKS BY ANATOLIY PERERVA - Tieliezhkina, Olesia (Philological Treatises, 2023)
The author of the proposed material emphasizes that the linguistic andstylistic organization of the artistic text has been of interest to linguists for a long time.However, the peculiarities of a poetic narrative expressive means functioning have notbeen deeply investigated so far. Therefore, the study of language units that testify to thestylistic potential in the poetic scope of Anatoliy Pererva is relevant since the writer’slinguistic world was not an object of a separate scientific analysis.The purpose of the investigation is to characterize the peculiarities of the representationof stylistic means of lexical and syntactic nature in the poetic works by Anatoliy Perervabased on the material of his collection “Nebesna yasnist”. The realization of the definedgoal involves the analysis of lexical and grammatical means of organizing the writer’spoetic narrative, the consideration of syntactic methods of his poetic languageexpressiveness, and the clarification of the stylistic potential of the revealed artistic andexpressive means in the formation of the linguistic fabric of the poetic text. Therefore, theobject of research is the language of Anatoliy Pererva's poetic collection “Nebesnayasnist”. The subject of the study is linguistic and artistic expressive and pictorial means oforganizing the language fabric of a poetic work, which have a lexical and syntactic origin.The researcher states that stylistic component of a lexical and grammatical andsyntactic nature are an organic part of the writer's poetic language space. And inparticular, those based on the repetition of components (polyptoton, adnomination,prosapodosis, antanaclasis, homeoteleuton, anaphora, epiphora,), opposition (antithesis,oxymoron), and accumulation (gradation).The scientist concludes that the mentioned figurative and expressive means have apowerful stylistic potential and contribute to the reproduction of the main motives of theconsidered collection (the rapidity of life, thoughts about the end of the earthly journey,love for mother and faith in God).